The Role of Vitamin D Deficiency as a Potential Risk Factor for Breast Cancer: A Case-Control Study - Aalia Amjad, Spogmay Humayun, Amir Hamza Khan, Tayyaba Ayaz, Warda Batool, Fareeha Afridi, Sabawoon Hayat (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the role of vitamin D deficiency as a risk factor for carcinoma breast. Study Setting: Khyber Teaching Hospital Peshawar in Khyber Pakhtunkhwa. Study Duration: Minimum of 6 months after approval of synopsis. Study Design: Case-control study Material and Methods: After taking approval from the hospital ethical committee, 256 patients were included in the study, between August 2022 and January 2023, divided equally into 2 groups as cases (breast cancer) and controls (breast diseases other than cancer). Vitamin D levels along with other variables were collected in Microsoft excel sheet and shifted to SPSS data base for analysis and the results shown in tables and charts. Results: The mean age for cases was 47.8 ± 11.6 SD and for controls was 33.7 ± 12.7 SD. The mean BMI for cases was 27.9 kg/m2 ± 3.3 and for controls was 26.6 kg/m2 ± 3.4. Other biological variables did not show much variation between both groups. The adjusted OR for cases showed significant association between low vitamin D levels OR 1.25 with 95% CI (0.74-2.12), p value 0.01 and higher BMIs OR 1.63 with 95% CI (0.96-2.75), p-value 0.05 with increased risk of breast cancer. Adjustment for age, sun exposure and use of vitamin D supplements did not show any significant association with risk of developing breast cancer. Conclusion: Since Vitamin D was found deficient in most of our study subjects, it can be considered as an independent risk factor in progression of breast cancer disease. Keywords: Vitamin D, breast cancer, risk factor.